Vezljivost poljskih glagolov s predpono w(e)- in slovenskih glagolov s predpono v- - Wtorkowska, Maria (Jezikoslovni zapiski, 2005)
On the basis of semantic-syntactical analyses of Polish and Slovene verbal derivatives the article discusses their valency and meaning, deterned by the prefix, and the functions the prefixes w(e)- and v- have in verbal derivatives.
Keywords: Slovene; slovenščina; poljščina; word formation; besedotvorje; glagol; verb; vezljivost